2017
DOI: 10.1063/1.4975219
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field effect on Poiseuille flow and heat transfer of carbon nanotubes along a vertical channel filled with Casson fluid

Abstract: Heat and mass transfer analysis of unsteady MHD nanofluid flow through a channel with moving porous walls and medium AIP Advances 6, 045222 (2016) (2005)] model has been used for effective thermal conductivity of CNTs. A uniform magnetic field is applied in a transverse direction to the flow as magnetic field induces enhancement in the thermal conductivity of nanofluid. The problem is modelled by using the constitutive equations of Casson fluid in order to characterize the non-Newtonian fluid behavior. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 49 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Hayat et al 36 reported mixed convection flow of Casson fluid with a magnetic field and temperature‐dependent thermal conductivity over a stretching cylinder by employing HAM. Aman et al 37 adopted the perturbation method to analytically investigate on heat transfer of single‐ and multi‐wall carbon nanotubes for convective Poiseuille stream on an upright conduit by considering water, kerosene, and engine oil. Amanulla et al 38 studied the mass and heat transmission effects from the surface of an isothermal sphere by utilizing the KBM.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al 36 reported mixed convection flow of Casson fluid with a magnetic field and temperature‐dependent thermal conductivity over a stretching cylinder by employing HAM. Aman et al 37 adopted the perturbation method to analytically investigate on heat transfer of single‐ and multi‐wall carbon nanotubes for convective Poiseuille stream on an upright conduit by considering water, kerosene, and engine oil. Amanulla et al 38 studied the mass and heat transmission effects from the surface of an isothermal sphere by utilizing the KBM.…”
Section: Introductionmentioning
confidence: 99%
“…Seth et al studied the unsteady MHD free natural convection and radiation effect on the flow of fluids over a moving vertically accelerated plate in the presence of chemical reaction. Apart from this study, many researchers had contributed to studying the unsteady MHD flow of Casson fluids past a flat plate with different boundary conditions. Vanita and Kumar studied the induced magnetic field effect over a vertical cone.…”
Section: Introductionmentioning
confidence: 99%
“…Halelfadel et al [7] examined the productivity of water-based nanofluid CNTs and deliberated the consequences of stumpy volume fraction nanoparticles in a range from 0.0055% to 0.278% on the physical properties (density, viscosity, thermal conductivity, and specific heat) of nanofluids. Aman et al [8] investigated the influence of magnetohydrodynamics on Poiseuille flow and heat analysis of CNTs with a Casson fluid vertical channel. Further studies on carbon nanotubes can be appraised in [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The density, specific heat capacity, and rate of thermal conductivities of the nanofluid [7,8] are expressed as:…”
mentioning
confidence: 99%